Redes sociais significativas de mães de filhos com transtorno do espectro do autismo - Colomé, Carolina Schmitt (2022)
The arrival of a child in the family provokes a series of in the family dynamics, demanding the reorganization of roles and work, social, domestic and child care tasks. However, when a horizontal stressor such as Autism Spectrum Disorder (ASD) is present in this scenario, such transformations can be intensified, especially for mothers, who are often referred to as the main caregivers in this context. Because of this, mothers of children with ASD can present high levels of burden, which points to the importance of significant social networks in this scenario, which can also be affected. Thus, this study aimed to understand the relational dynamics of significant social networks of mothers of children with ASD, based on its configuration in terms of structure, functions and multidimensionality of ties. In addition, we sought to identify the meanings attributed to the significant social network by mothers of children with ASD and how the birth of a child with ASD affected the maternal significant social networks. Therefore, a qualitative, descriptive exploratory and transversal research, based on the Grounded Theory of Data (TFD) was carried out. Twelve mothers of children diagnosed with ASD in childhood participated, with which reflective interviews were conducted and the instrument of the map of significant social networks was applied. Data analysis took place through the steps of open, focused, axial and theoretical coding, from which three categories were listed, which gave rise to three articles: 1. Configuration of significant social networks; 2. Relational dynamics of significant social networks and 3. Meanings attributed to significant social networks. The results revealed the predominance of large networks, medium density, smaller distribution than before the ASD, but greater dispersion, heterogeneity and multidimensionality. The functions were adjusted to the new reality of ASD. However, mothers do not feel the support of network members as effective, which can be understood from the consideration of the phenomena of a) maternal closure to share care and b) closure of the network to offer the necessary help. Thus, the presence of members in the network does not correspond to the quality of support they provide. In this scenario, both the social ideal of perception of maternal care as qualitatively superior and more adequate, as well as the lack of knowledge about the ASD, were identified as important factors in both closure phenomena, causing voluntary and involuntary withdrawals. Thus, the importance of democratizing access to knowledge about ASD in society and the deconstruction of stigmas related to the maternal role are emphasized. Still, the map of significant social networks is pointed out as a powerful tool to support intervention strategies in the context of health promotion, indicating the familiarization of health, education and social care professionals with the instrument, in order to be able to apply it, mapping the social network of families who receive ASD diagnosis, strengthening them and activating the ties to provide the necessary support.